Little altars everywhere - Wells, Rebecca, 1952- (New York : HarperPerennial, 1996)
Little Altars Everywhere is a national best-seller, a companion to Rebecca Wells' celebrated novel Divine Secrets of the Ya-Ya Sisterhood. Originally published in 1992, Little Altars introduces Sidda, Vivi, the rest of the spirited Walker clan, and the indomitable Ya-Yas. Told in alternating voices of Vivi and her husband, Big Shep, along with Sidda, her siblings Little Shep, Lulu, Baylor, and Cheney and Willetta — the black couple who impact the Walkers' lives in ways they never fully comprehend — Little Altars embraces nearly thirty years of life on the plantation in Thorton, Louisiana, where the cloying air of the bayou and a web of family secrets at once shelter, trap and define an utterly original community of souls. Who can resist such cadences of Sidda Walker and her flamboyant, secretive mother, ViVi? Here the young Sidda — a precocious reader and an eloquent observer of the fault lines that divide her family — leads us on a mischievous adventures at Our Lady of Divine Compassion parochial school and beyond. A Catholic girl of pristine manners, devotion, and provocative ideas, Sidda is the very essence of childhood joy and sorrow. In a series of luminous reminiscences, we also hear Little Shep's stories of his eccentric grandmother, Lulu's matter-of-fact account of her shoplifting skills, and Baylor's memories of Vivi and her friends, the Ya-Yas. Beneath the humor and tight-knit bonds of family and friendship lie the undercurrents of alcoholism, abuse, and violence. The overlapping recollections of how the Walkers' charming life uncoils to convey their heart-breaking confusion are oat once unsettling and familiar. Wells creates an unforgettable portrait of the eccentric cast of characters and exposes their poignant and funny attempts to keep reality at arm's length. Through our laughter we feel their inevitable pain, with a glimmer of hope for forgiveness and healing. An arresting combination of colloquialism, poetry, and grace, Little Altars Everywhere is an insightful, piercing and unflinching evocation of childhood, a loving tribute to the transformative power of faith, and a thoroughly fresh chronicle of a family that is as haunted as it is blessed.
Keywords: Catholics -- Fiction; Dysfunctional families -- Fiction; Louisiana -- Fiction; Domestic fiction